Harnessing fear of predators and competitors as deterrents for an invasive predator - Sze Wing Yiu; Justin P. Suraci; Grant Norbury; Patrick M. Garvey (Ecosphere)
Abstract Manipulation of animal behavior is a powerful tool for nonlethal wildlife management where lethal control is not possible. Animal behavior is driven by motivations to acquire food and mates and to avoid predation, and animals utilize their sensory systems to obtain information and assess perceived risks. It is therefore possible to achieve management objectives by exploiting animal motivation and risk assessment by using sensory cues to trigger behavioral responses. Domestic cats (Felis catus) are invasive predators contributing to global biodiversity loss, but cat management is controversial because cats are valued as companion animals. To develop a nonlethal approach to reduce cat impacts on native biodiversity, we conducted playback experiments and manipulated risks perceived by cats using auditory cues from a predator (humans) and competitors (domestic dog Canis familiaris and cats). We tested the effectiveness of sound cues to induce fear behaviors and deter cats from food patches in captive and urban environments. Human playbacks protected the greatest proportion of food patches, were more likely to reduce time spent feeding, and induced fleeing responses and spatial avoidance to a greater degree than competitor or control treatments. Human playbacks had a similar impact on both captive and free‐roaming urban cats. Cat and dog playbacks were effective in protecting food patches but induced fewer fear responses. Habitat complexity reduced the level of perceived risk and cat responses. Our study demonstrated the efficacy of using audio playbacks as deterrents for cats, and we are currently integrating playbacks into a management tool to repel cats from areas where they are not wanted but lethal control is not feasible.